Floodwater Harvesting for Groundwater Recharge: Techniques, Challenges and Applications - Hesham Ezz (Geography, Earth Science and Environment: Research Highlights Vol. 6, 2025)
Climate change, rapid urbanization, and population growth have intensified global water scarcity, increasing reliance on groundwater resources. One of the most effective solutions to this crisis is artificial groundwater recharge through floodwater harvesting, which captures surface runoff and facilitates controlled infiltration into aquifers. Floodwater harvesting techniques, such as check dams, recharge basins, and injection wells, are designed to capture and store excess runoff, allowing controlled percolation and groundwater replenishment. This study provides a comprehensive review of artificial groundwater recharge techniques, categorizing them into surface (spreading), sub-surface, and indirect methods. A total of eleven techniques were analyzed, including recharge basins, check dams, injection wells, and induced recharge methods, which have been successfully implemented in various regions. The review highlights the benefits of artificial recharge, such as improved groundwater storage, reduced soil erosion, and enhanced water quality. However, challenges such as aquifer contamination, sediment clogging, and inefficient recharge structures remain significant barriers to implementation. The study also examines the environmental impacts of artificial recharge, addressing both positive aspects (such as ecological restoration and energy savings) and potential drawbacks (including land subsidence and aquifer pollution risks). A special focus is given to Egypt, where floodwater harvesting has been implemented in Sinai using check dams and surface recharge techniques. Despite its potential, groundwater recharge in Egypt remains underutilized, necessitating further research into sub-surface recharge methods and alternative energy solutions such as solar-powered recharge systems. The findings emphasize the need for integrating hybrid recharge methods, optimizing energy-efficient approaches, and assessing long-term environmental impacts to enhance recharge sustainability and support global water security efforts.